منقولہ اشیاء کا وقف:شرعی جائزہ: Waqf of mobile assets: Sharia Overview - Syed Hayatullah; Anjum Riaz; Fozia Yaseen (AL-IDRAK JOURNAL, 2024)
The Arabic word waqf (endowment) implies to stop, hold, quiet down, confine, or obstruct. According to sharia, waqf refers to reserving the right to property (al-'ain) from the donor with the intention of transferring its advantages (al-manfa'ah) to the donor's designated waqf recipient or to the benefit of Muslims or religious interests. In the context of Islamic law, waqf is the giving or transferring of ownership rights over an asset to a designated use, typically for generous or public purposes. The waqf asset may take the shape of real estate, structures, or other assets. When Muslims give waqf, they usually don't plan to take back the property, building, or money that was increased from them. Withholding funds and using them as investment gains is what is meant to be done with a cash endowment. The mobile assets endowment is a conflicted issue amongst the jurists. The Hanafi jurists permitted it with a few restrictions while the shawafe and hanabala do not consider any difference amongst the mobile and immobile assets in the perception of endowment. According to the modern Islamic jurists cash endowment is permissible because the reasonable aim of the endowment which is to take hold of the asset and channel the profit gained from it, and because money is replaced for it not being specified by designation.